Loco-regional drug delivery in oncology: current clinical applications and future translational opportunities. (4th May 2021) - Rossi, Seona M.; Murray, Timothy; McDonough, Liam; Kelly, Helena
ABSTRACT: Introduction : Drug-based treatment regimens for cancer are often associated with off-target toxic side effects and low penetration of the drug at the tumor site leading to patient morbidity and limited efficacy. Loco-regional drug delivery has the potential to increase efficacy while concomitantly reducing toxicity. Areas covered : Clinical applications using loco-regional delivery include intra-arterial drug delivery in retinoblastoma, direct intra-tumoral (IT) injection of ethanol for ablation in hepatocellular carcinoma (HCC) and the use of HIPEC in peritoneal carcinomas. In recent years, there has been a significant increase in both approved products and clinical trials, with a particular emphasis on drug delivery platforms such as drug-eluting beads for HCC and hydrogel platforms for intravesical delivery in bladder cancer. Expert opinion : Development of loco-regional drug-delivery systems has been slow, limited by weak clinical data for early applications and challenges relating to dosing, delivery and retention of drugs at the site of action. However, there is increasing focus on the potential of loco-regional drug delivery when combined with bespoke drug-delivery platforms. With the growth in immunotherapies, the use of IT delivery to drive priming of the anti-tumor response has opened up a new field of opportunity for loco-regional drug delivery.